Development of droplet characteristics prediction models for air induction nozzles based on wind tunnel tests - Liao, Juan; Hewitt, Andrew John; Wang, Pei; Luo, Xiwen; Zang, Ying; Zhou, Zhiyan; Lan, Yubin; O’Donnell, Chris (International Journal of Agricultural and Biological Engineering, 2019)
Nozzle flowrate and spray pressure are two of the most important factors influencing on droplet characteristics. With the aim to develop prediction models for air-induction nozzles (AINs), a series of Billericay Farm Services (BFS) AINs with different orifice diameters in combination with tap water were tested. 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa and 0.7 MPa of spray pressures and 2 m/s, 3 m/s, 4 m/s and 5 m/s of air speeds were setup. Based on the wind tunnel tests data, prediction models with input variables of nozzle flowrate and spray pressure and output variables of Dv0.1, Dv0.5, Dv0.9, %<150 µm (proportion of spray volume contained in droplets with diameter below 150 µm), relative span (RS) and coefficient of variation (CV) of Dv0.5 were developed. The developed models were validated based on wind tunnel experimental data. Results showed that: for Dv0.1, Dv0.5, Dv0.9 and %<150 µm, R2 were equal to 0.768, 0.823, 0.868 and 0.811, indicating that the predictive ability for these four parameters were strong. For RS and CV, R2 were equal to 0.100 and 0.113, respectively, indicating that the predictive ability for these two parameters were poor. The models developed in the present study are helpful for facilitating the use of AIN in agricultural spray application. Keywords: prediction model, agricultural spray application, droplet characteristics, AIN, laser diffraction DOI: 10.25165/j.ijabe.20191206.5014 Citation: Liao J, Hewitt A J, Wang P, Luo X W, Zang Y, Zhou Z Y, et al. Development of droplet characteristics prediction models for air induction nozzles based on wind tunnel tests. Int J Agric & Biol Eng, 2019; 12(6): 1–6.